In the shadow of the blade - Fries, Patrick; Fries, Cheryl; Arrowhead Film & Video; Fabrication Films ([Austin, TX] : Arrowhead Film & Video, 2004)
This emotion-packed documentary follows the 10,000-mile journey of a battle-scarred UH-1 "Huey" helicopter into America's backyards to hear the untold stories of America's Vietnam War veterans and the families who waited for them to come home. The evocative healing power of this film has been described as "the most important thing to happen to Vietnam veterans since the dedication of The Wall."
Distributed by Fabrication Films.
Not rated.
DVD.
Keywords: Vietnam War, 1961-1975 -- Veterans -- United States; HueyCobra (Helicopter)